An unusual case of stroke in a young patient. Issue 2 (24th January 2007) - Verghese, Saeda; Nair, Sabarinath B; Keep, Jeff
Abstract : The patent foramen ovale (PFO) has been increasingly implicated in the aetiology of stroke, particularly in young patients with no other identifiable cause (cryptogenic stroke). A case of Parinaud's syndrome secondary to thromboembolism from a PFO is reported here.